A NEW APPROACH TO THE DIAGNOSIS AND TREATMENT OF PATIENTS SUFFERING FROM ALLERGIC SKIN DISEASE - Salamova L.A. (PEDAGOGS, 2024)
Abstract: the scientific search for new technologies for the restorative treatment of patients with itchy dermatoses is associated with their etiopathogenetic factors that have not yet been sufficiently studied, determining the polymorphism of clinical manifestations of this pathology, where domestic and foreign researchers include contact dermatitis (L 23), eczema (L 20.8), prurigo (L 28.1, i.e. nodular pruritus; L 28.2, i.e. papular urticaria); allergodermatitis caused by substances taken orally, as well as other nosological forms of dermatoses, united by a single category of diseases of the XII class according to the ICD-X. The problem of innovation of existing standard approaches is actualized by the fact that the level of allergization of various social groups of the population "is in direct correlation with the increasing environmental pollution of the environment. This not only makes the clinical picture of the course of itchy dermatoses heavier, but also provokes their recurrent nature, lengthening the period of disability of patients with this skin pathology, and in 9-11% leading to disability.